Kekuatan Instagram dengan Electronic-Word-of-Mouth (Ewom) dan Influencer dalam Komunikasi Pemasaran - Gultom, Atikah Putri Adrilia; Irwansyah, Irwansyah (Jurnal InterAct, 2021)
Social media has the power to change the patterns of people interacting and communicating. The growth use of Social Networking Sites/SNS has also led to changes in the communications industry, one of this is the integration of communication and marketing. This study aims to understand how the power of Instagram with eWOM and influencers that focus on the beauty and lifestyle in the digital era when conducting communication and marketing activities for one of the beauty products brands. The method in this study uses a “qualitative approach”, while data collection uses the “Indepth Interview” technique. Interview process using the Zoom application on two informants who were actively using Instagram, had used social media for eWOM, had a minimum number of followers was 1000, and focused to the development of beauty trends in Indonesia. The results of this study indicate that currently the brand not only focus on eWOM and influencers with a large number of followers, but also focus to the scope and closeness of influencers with their followers. The eWOM activities carried out by influencers with reviews based on experience. The variety of eWOM is divided into two, sponsored and not sponsored.